Marine terminating ice-stream retreat within the Eyjafjarðaráll basin, North Iceland; documented by multibeam bathymetric and high-resolution Chirp reflection data - Bailey OConnell 1994- (2020)
The behavior and retreat of the Icelandic Ice Sheet (IIS) is not well understood and research done on the shelf can help refine ice sheet models. Multibeam bathymetric maps and Chirp shallow-reflection data offshore N-Iceland provide some answers to long-standing questions about the extent of the Iceland ice sheet during the Last Glacial Maximum (LGM) and early deglaciation of the Eyjafjarðaráll ice stream. The glacially eroded Eyjafjarðaráll rift basin (EB) is ~80 km NS and 15-20 km wide EW and made up of complex extensional (normal) and transform (strike-slip) faults draped by ice-marginal and subglacial sedimentary features, megascale glacial lineations (MSGLs), moraines, eskers, and unidentified complex till ridge features, which have not been previously described in literature, possibly representing a push moraine or lateral crevasse-squeeze ridges. These features reflect the past ice flow directions of at least two major ice streams, from Skagafjörður into Skagafjarðardjúp and from Eyjafjörður into the southern Eyjafjarðaráll basin. These ice streams merged in the northern Eyjafjarðaráll basin, where the more prominent Skagafjörður ice stream deflected the Eyjafjarðaráll ice stream. The megaflutes are orientated parallel to the direction of the major basins and the Kolbeinsey Ridge indicating that the ice streams were topographically constrained. Similar lineations are also present within Skjálfandadjúp, east of Eyjafjarðaráll. The highly reflective V-shaped ridges are characterized by elongated “V-shape” formations with an average width of 300-500 m and an average length ranging from 400-1500 m, at a depth of 320-450 meters b.s.l. opening towards the flow direction of the main ice stream. The ridges change direction gradually, along with the basin curvature, from NNW-SSE in the southern part of the basin rotating to NNE-SSW, parallel to a 10 km long lateral moraine, which most likely separated two main ice streams. These ridges have not been identified elsewhere. The seafloor also bears ample scars made ...